2021
DOI: 10.1136/bmjopen-2021-048856
|View full text |Cite
|
Sign up to set email alerts
|

The UPTAKE study: a cross-sectional survey examining the insights and beliefs of the UK population on COVID-19 vaccine uptake and hesitancy

Abstract: ObjectiveA key challenge towards a successful COVID-19 vaccine uptake is vaccine hesitancy. We examine and provide novel insights on the key drivers and barriers towards COVID-19 vaccine uptake.DesignThis study involved an anonymous cross-sectional online survey circulated across the UK in September 2020. The survey was designed to include several sections to collect demographic data and responses on (1) extent of agreement regarding various statements about COVID-19 and vaccinations, (2) previous vaccination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 28 publications
(39 reference statements)
7
21
0
Order By: Relevance
“…Most (97%) of the studies included in our review employed a web-based recruitment method for data collection [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] . Only one study used a face-to-face data collection method, and one used both face-to-face and web-based data collection methods [87] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most (97%) of the studies included in our review employed a web-based recruitment method for data collection [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] . Only one study used a face-to-face data collection method, and one used both face-to-face and web-based data collection methods [87] .…”
Section: Resultsmentioning
confidence: 99%
“…For both time periods, 17 studies that compared women vs. men reported that men were more likely to accept the COVID-19 vaccine [41] , [43] , [46] , [47] , [52] , [56] , [61] , [62] , [65] , [72] , [74] , [75] , [76] , [81] , [83] , [85] , [88] ; however, in four studies, women were more likely to accept the COVID-19 vaccine [39] , [75] , [86] , [93] . Older age was associated with increased COVID-19 vaccine uptake compared to younger age [35] , [38] , [50] , [52] , [53] , [57] , [64] , [74] , [75] , [76] , [85] , [86] , [90] , [92] , [95] , [100] , and this result was stable across the time periods, with six studies reporting higher uptake in younger age groups [39] , [43] , [47] , [62] , [65] , [94] . Across both periods, 18 studies found that education levels correlated positively with COVID-19 vaccine uptake [35] , [46] , [49] , [52] , [53] , [57] , [59] , [60] , [63] , [67] , [68] , [74] , [76] , [85] , [88] , [90] , …”
Section: Resultsmentioning
confidence: 99%
“…Our models also included variables for smoking prevalence and adult obesity, drawn from the 2021 CHRR data 29 . Studies have shown that smoking and obesity are associated with vaccination rates, though findings have been inconsistent 41–43 . Smoking prevalence was defined as the percentage of adults in the county who reported currently smoking, and adult obesity was the percentage of adults in the county who reported having a body mass index greater than or equal to 30 kg/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Whilst this could suggest that choice inadvertently impedes vaccine uptake, it is pertinent to note that, in the US, political views can strongly influence vaccine uptake as according to Albercht (2022) Trump supporters are far less likely to be accepting of vaccination. In the UK, where the political scene is different and there's greater emphasis on healthcare solidarity, the most common reason for vaccine hesitancy stems from concern over vaccine side effects (60%; Sethi et al, 2021). Therefore, direct comparisons between the US and UK political and healthcare landscapes cannot easily be drawn.…”
Section: Empirical Datamentioning
confidence: 99%